The Rule of Hessenberg Matrix for Computing Determinant of Centrosymmetric Matrices - Khasanah, Nur; Kuntarini, Agustin Absari Wahyu (CAUCHY, 2020)
The application of centrosymmetric matrix on engineering take their part, particulary about determinat rule. This basic rule needs computational process for determining appropiate algorithm. Therefore, by the algorithm of determinant kind of Hessenberg matrix, this is used for computing determinant of centrosymmetric matrix more efficiently. This paper shows the algorithm of lower Hessenberg and sparse Hessenberg matrix to construct the efficient alforithm of determinant of centrosymmetric matrix. By using the special structure of centrosymmetric matrix, the algorithm of these determinant are usefull for their own characterstics.